2022
DOI: 10.1038/s41396-022-01308-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant-associated fungi support bacterial resilience following water limitation

Abstract: Drought disrupts soil microbial activity and many biogeochemical processes. Although plant-associated fungi can support plant performance and nutrient cycling during drought, their effects on nearby drought-exposed soil microbial communities are not well resolved. We used H218O quantitative stable isotope probing (qSIP) and 16S rRNA gene profiling to investigate bacterial community dynamics following water limitation in the hyphospheres of two distinct fungal lineages (Rhizophagus irregularis and Serendipita b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 96 publications
0
9
1
Order By: Relevance
“…There was a positive correlation between aridity and bacteria‐fungi associations in the topsoil, but we observed an opposite correlation in the deep soil (Figure S14). As we know, when water availability is scarce, plant‐associated fungi can support bacterial resilience through fungal‐bacterial synergies (Hestrin et al., 2022), and then induce species coexistence (Lozano et al., 2021; Zelezniak et al., 2015). For example, interactions between rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF) using plants as a medium can induce plant tolerance to water limitation (De Vries et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive correlation between aridity and bacteria‐fungi associations in the topsoil, but we observed an opposite correlation in the deep soil (Figure S14). As we know, when water availability is scarce, plant‐associated fungi can support bacterial resilience through fungal‐bacterial synergies (Hestrin et al., 2022), and then induce species coexistence (Lozano et al., 2021; Zelezniak et al., 2015). For example, interactions between rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF) using plants as a medium can induce plant tolerance to water limitation (De Vries et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These results show that AMF has an important role in reducing drought stress in soil ecosystems. AMF can maintain soil moisture stability under drought stress conditions, ensuring that the microorganism community surrounding the root area is not adversely affected (Bahadur et al 2019;Hestrin et al 2022). However, under normal conditions, the AMF inoculation did not show a significant effect on the increase in total soil microbial activity.…”
Section: Soil Microbial Activitymentioning
confidence: 93%
“…However, research on the effects of AMF application on soil microbial communities is still scarce. AMF has been shown to not only improve the adaptability and resistance of its host plants but also to maintain the stability of the soil microbi-al community (Hestrin et al 2022). Hestrin et al (2022) demonstrated that applying AMF simultaneously can provide a protective effect on soil microbial communities exposed to drought stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria can also attach to non-living hyphae and use them as a substrate (Toljander et al, 2006(Toljander et al, , 2007. Our prior work suggests AMF have diverse effects on nearby hyphosphere microbiomes: stimulating organic matter decomposition and nitrogen (N) transfer (Nuccio et al, 2013), supporting water transport (Kakouridis et al, 2022) and drought resilience (Hestrin et al, 2022), and stimulating cross-kingdom trophic interactions (Nuccio et al, 2022). However, these small-scale interactions can be difficult to directly measure, and under native soil conditions, it is particularly challenging to directly evaluate the hyphosphere effects without the influence of roots and rhizosphere organisms.…”
Section: Introductionmentioning
confidence: 99%